Optimizing Performance of Turjawali Satsamapta Unit Polres Grobogan Through Four-Wheeled Patrols to Prevent Burglary - Ansori, Alif Sulthan Faisal (Advances in Police Science Research Journal, 2024)
Burglary is theft with specific qualifications (gequalificeerde deifstal) which is committed in a certain way and in any condition that classified to extreme category so can be punished with maximum penalty of more than 5 years in prison as regulated in article 363 KUHP. Based on data of the Police Report of the Criminal Investigation Unit Polres Grobogan, Burglary, known as “Curat”, is a crime that currently dominates the Number of Criminal Acts (NCA) compared to other crimes. As we noted that in 2020 there were 60 cases, in 2021 there were 42 cases and in 2022 there were 73 cases. Therefore, increment of burglary in 2022 requires an idea to solve and or reduce immediately. Thus, as a preventive action for Burglary cases, Polres Grobogan attempt to actively arrange four-wheeled Patrol that carried out by the Turjawali Satsamapta Unit. Polres Grobogan is working hard on the fourwheeled Patrol because it is considered to be running quite well but still requires improvements in its implementation due to internal and external factors in the field. SOP (Standard Operating Procedure) regarding patrol for four-wheeled patrol activities is guided by the Regulation of the Head of the Security Maintenance Agency for the Indonesian National Police Number 1 of 2017 about Patrols. Every result of human action always has its motives that encourage perpetrators to do crime. Many factors cause an increase burglary by criminals. Several factors that caused burglary are the economic factors of the criminals, the condition of society who are negligent about securement and quiet places that give opportunities for criminals to carry out their actions. In this case, it is necessary to analyze and evaluate to optimize the performance of Turjawali Satsamapta Unit Polres Grobogan through four-wheeled patrol to prevent Burglary.